2020
DOI: 10.1021/acs.jpclett.0c03208
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Solvent-Related Reactions and Corresponding Band Gap Tuning Strategies for Carbon Nanodots Based on Solvothermal Synthesis

Abstract: The role of the solvent in the solvothermal synthesis of carbon nanodots (CDs) is a long-standing puzzle for comprehensively understanding the CD formation mechanism and the relevant band gap tuning phenomenon. The controversy regarding solvent effect continues, largely because the importance of solvent-related reactions (SRs) has been ignored. In this Letter, we report that the SRs, i.e., oxidation-assisted solvent-involved dehydration and solvent-promoted oligomerization of phenylene/pyridinediamine (PD/PyD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“… 43 Therefore, the effects of doping and strain may account for the variation in the Raman spectra. 48 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 43 Therefore, the effects of doping and strain may account for the variation in the Raman spectra. 48 …”
Section: Resultsmentioning
confidence: 99%
“…Although the veritable mechanism of fluorescent carbon dots is remain strongly debated, it has been confirmed that the photo-physical performances of CDs rely on the HOMO–LUMO energy gap, and the heteroatomic doping could tune the PL bandgap through expanding the conjugated field of the fluorophores. 48 The N and S atoms with many lone pair electrons lead to the availability of multiple isolated sp 2 conjugated carbon clusters. And isolated sp 2 conjugated carbon clusters can serve as valid radial centers enhancing the fluorescent performances of the CDs-IPM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, various solvents can be divided into three categories for analysis. [61][62][63] First, the strongest emission peak position of the CDs shows an obvious redshi with the gradual increase of the polarity of the solvent, accompanied by a decrease in uorescence intensity, when the protic solvent does not have functional groups (such as -OH and -COOH) that easily form hydrogen bonds (Fig. S9a †).…”
Section: Ethanol Responsiveness Of the Cdsmentioning
confidence: 99%
“…17,18 Synergistic effects will occur when the fluorescence emissions of CPDs are regulated by the size of the sp 2 domain and the surface states. 19,20 Notably, most luminescence mechanisms of CPDs prepared from organic monomers by the bottom-up method are derived from synergistic effects. 21–23…”
Section: Introductionmentioning
confidence: 99%